Beautiful Shells and their Connection to the Reef - Grant, Chrissy (Queensland Review, 2021)
Shells are beautiful! They are really ingenious in the way that they are made and the animals they house. The shells grow with the animal, from tiny little shells to a great big shell. An animal wasn’t born that big, so the large shells have been there for years.